The Use of Telang Flower Extract (Clitoria ternatea L.) as a Natural Universal pH Indicator coupled with Digital Image Colorimetry - Esterlin; Nursaadah, Euis; Wardana, Rendy W.; Firdaus, M. Lutfi (PendIPA Journal of Science Education, 2024)
The acid base indicators commonly used by scientists are mostly synthetic indicators that are harmful for the environment.Moreover, chemists need various chemicals to detect broad pH ranges for acid and base samples solution.  The aim of this research was to create a natural universal pH indicator from telang flower (Clitoria ternatea L.) extract coupled with the digital image detection. The universal pH indicator is very important in education chemistry that broadly used for titration and other class room chemical experiments. This process of making a natural universal pH indicator integrated with digital images meets green chemistry criteria that use environmentally friendly materials and technology. The results show that color absorption data at pH 1-2 are purple, pH 3-5 are violet, pH 6-10 are blue, pH 11-12 are green and pH 13-14 are yellow. RGB intensity digital image data shows the intensity of the red color increases in the pH range 6-11, while the intensity of the green and blue colors tends to be stable. The proposed method was validated using a UV-Vis spectrophotometer and conventional pH meter that give the comparable results.